2008
DOI: 10.1007/s00213-008-1238-0
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D4 receptor involvement in the discriminative stimulus effects in rats of LSD, but not the phenethylamine hallucinogen DOI

Abstract: Rationale Lysergic acid diethylamide (LSD) differs from other types of hallucinogens in that it possesses direct dopaminergic effects. The exact nature of this component has not been elucidated. Objective The present study sought to characterize the effects of several dopamine D 4 agonists and antagonists on the discriminative stimulus effect of LSD at two pretreatment times and 2,5-dimethoxy-4-iodoamphetamine (DOI), a selective 5-HT 2A/2C agonist. Materials and methods Male Sprague-Dawley rats were trained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 54 publications
(75 reference statements)
0
34
0
Order By: Relevance
“…Racemic 9b had an EC50 of 74 nM and 73% intrinsic activity, being close to a full agonist relative to 5-HT. Furthermore, in rats trained to discriminate between intraperitoneal LSD (0.08 mg/kg) and saline, with a 30 min pretreatment time (LSD-30), 19 the racemate showed full substitution at low doses, as did the positive control 1. We were encouraged by the fact that the dosage required for a 50% response when using the constrained analogue was about onehalf that required for the control, 1, which translates into close to a 3-fold increase in molar potency in vivo (Table 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Racemic 9b had an EC50 of 74 nM and 73% intrinsic activity, being close to a full agonist relative to 5-HT. Furthermore, in rats trained to discriminate between intraperitoneal LSD (0.08 mg/kg) and saline, with a 30 min pretreatment time (LSD-30), 19 the racemate showed full substitution at low doses, as did the positive control 1. We were encouraged by the fact that the dosage required for a 50% response when using the constrained analogue was about onehalf that required for the control, 1, which translates into close to a 3-fold increase in molar potency in vivo (Table 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As recently outlined in an excellent review on the pharmacology of hallucinogens (Nichols 2004), serotonin 2C receptor (5-HT 2C ) agonism, 5-HT 1A agonism, and SERT uptake inhibition have all been implicated in the activity of hallucinogens. Dopamine (DA) receptors (Marona-Lewicka et al 2009; Marona-Lewicka et al 2005; Seeman et al 2005), the trace amine receptor (Bunzow et al 2001) and the sigma-1 receptor (Fontanilla et al 2009; Su et al 2009) have also been suggested to modulate the effects of hallucinogenic compounds. The hallucinogen salvinorin A ( 10 ), a natural product derived from Salvia divinorum or “magic mint” was unexpectedly found to be a highly selective kappa opioid receptor agonist (Roth et al 2002), providing yet another possible neurochemical pathway for psychoactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the hypothesis that the dopaminergic system could be involved in the effects of LSD caught the attention of other researchers. LSD binds to the D 1 and D 2 receptors as a partial agonist [120], and the D 4 receptor as a full agonist [124]. In particular, LSD shows high affinity ( k i = 2 nM) for D 2 receptors in both pig brain [57] and in human cloned D 2 receptors [50,59].…”
Section: In the Deep Of The Mechanism: Who Are The Players?mentioning
confidence: 99%